Burden and predictors of heart failure treatment outcomes in Ethiopia: A systematic review and meta-analysis protocol. - Firomsa Bekele; Lalise Tafese; Bayisa Garbessa; Shimalis Tadasa; Ginenus Fekadu (PLoS ONE)
Background Heart failure is an important global health problem which is associated with high mortality. Uncontrolled heart failure leads to hospitalization and reduction in quality of life. Therefore, the study aimed to assess the treatment outcome such as improved, death, hospitalization, and self-discharges without improvement and associated factors in heart failure patients admitted to south western Ethiopian hospitals. Methods We will use databases such as PubMed, Science Direct, HINARI, Scopus and Google Scholar. The final systematic review and meta-analysis will contain papers that fulfill the eligible criteria. A systematic data extraction check list will be used to extract the data, and STATA version 14 will be used for the analysis. Heterogeneity is evaluated using the I2 tests and the Cochrane Q test statistic. To examine publication bias, a funnel plot, Egger's weighted regression, and Begg's test are utilized. The sensitivity analysis and subgroup analysis will be done for studies having heterogeneity. The Joanna Briggs institute meta-analysis of statistics assessment and review instrument (JBI- MAStARI) will be used for quality assessment. Discussion This protocol is expected to provide adequate evidence on the burden of poor heart failure treatment outcome that includes self-discharge, developing complication and finally leads to death in acute and chronic heart failure patients in Ethiopia. Furthermore, to enrich our estimation, we also intended to assess the associated factors of poor treatment outcome. Therefore, our review will call for government and non-government interventions in reducing the mortality associated with heart failure.